The regular open-open topology for function spaces - Kathryn F. Porter (International Journal of Mathematics and Mathematical Sciences)
The regular open-open topology, Troo, is introduced, its properties for spaces of continuous functions are discussed, and Troo is compared to Too, the open-open topology. It is then shown that Troo on H(X), the collection of all self-homeomorphisms on a topological space, (X,T), is equivalent to the topology induced on H(X) by a specific quasi-uniformity on X, when X is a semi-regular space.